PENGEMBANGAN USAHA PETERNAKAN SAPI BALI MELALUI PENERAPAN SISTEM AGRIBISNIS DI KABUPATEN GOWA - Fatimah, Fatimah; Rahim, Rahman (COMPETITIVENESS, 2019)
AbstractThis study aims to find out (1) The Development of Demand for Balinese Beef (2) the feasibility of Bali Cattle business and (3) the prospect of agribusiness development of Bali Cattle.The research was conducted in Tombolo Pao subdistrict and Pallangga District, Gowa Regency. The determination of the research location was done deliberately and the selection of samples was determined randomly, namely 76 farmers respondents from a total population of 320 farmers.  Data collection is done by direct interview, observation and documentation. The data was analyzed using trend analysis, R/C Ratio analysis and SWOT analysis.The results showed that the demand for Balinese beef is projected to increase by 125,461 kg per year.  Bali Cattle farming business is worth trying because it can provide benefits to farmers of Rp. 3,938,881.4 kg per year or Rp. 328,240 per month with an R/C Ratio of 1.41.  The prospect of bali cattle development based on strength and opportunities has good prospects to be developed. Keywords: Bali Cattle Farming Business and Agribusiness System Implementation.